Penerapan Analitycal Hierarchy Process (Ahp) dalam Menentukan Lokasi Pabrik Tempe - Cahyaning Kilang Permatasari (Institut Teknologi Sains Bandung, 2020)
Nowadays, tempe household industry entrepreneurs must choose the right factory location. Location is very influential for develop of a company, besides it can minimize problems in the future. The purpose of this study was to determine the percentage of priority criteria in selecting factory locations. The results of the calculation of priority criteria, it is hoped that entrepreneurs will find it easier to determine a suitable location to build a tempe factory. This research was conducted in Karanganyar Regency. The method used to determine the priority criteria for selecting the tempe factory location is Analytical Hierarchy Process (AHP) method. After through the process of obtaining data and analyzing calculations using Microsoft Excel, the percentage result of the criteria are geological and climatic conditions (34.67%), availability of labor (26.94%), market and marketing distance (14.93%), transportation facilities (11.36%), supporting facilities and utilities (7.08%) and distance to the location of raw material suppliers (5.02%). This criterion combines several aspects based on the level of importance, so that the results of the order in selecting the location of the tempe factory will be more objective